A Review on Cyperus rotundus: Ancient Weed to Modern Elixir of Life Phytochemistry and Therapeutic Uses of Cyperus rotundus (Mustaka) - Hemanth Kumar Kandikattu; Farhath Khanum; Narayanappa Amruta; V.V.P.C. Narayana; Doddaga Srinivasulu (Mazandaran University of Medical Sciences, 2021)
Background: Since time immemorial, humans have identified several herbs to treat various ailments. With the advancement of science and state-of-the-art technologies, different herbal extracts and chemical constituents of herbs were identified as therapeutic targets. Cyperus rotundus, also called mustaka, is one of the most ancient herbs widely distributed in tropical and subtropical regions across the globe. The tuberous and aerial parts of the herb were identified to possess various pharmacological properties. Objectives: This review focuses on the various phytocompounds of mustaka and how these compounds exert pharmacological effects and their mode of action. The molecular and cellular effects of mustaka were also discussed based on the preclinical and clinical reports available using an array of in vitro, in vivo, and ex vivo methodologies. Methods: The information from Google Scholar, Science direct, PUBMED, were reviewed with a special focus on the mode of action of C. rotundus from the data on animal and pre-clinical experiments to treat various diseases. Conclusion: Based on the literature available on C. rotundus in Google Scholar, Science Direct, and PubMed, the pharmacological properties of mustaka were reviewed with a particular focus on its neuropharmacological activities. The mode of action of C. rotundus and its bioactive metabolites at the molecular biology level were demonstrated based on animal and preclinical experiments to cure various ailments. These diverse effects prove C. rotundus as a valuable traditional medicine for treating various disorders.